Towards the resuscitation of the use of traditional songs and educative media jingles to boost morals in Nigerian schools (2025)
This diopter investigated the complexity of modem Nigerian youth and morality in die context of social networks. Idealism, energy and ambitions fo r desired change have been observed as features of the conflict between the youth and the society. However, the moral standards of young people and their general ethical tendencies are perceived as portraying a dark image of today and future generations. Young people in particular are increasingly divorcing themselves from the enduring cultural principles; the change is further amplified by the social networking sites. It has been postdated that technology has a great influence on the realms of morality due to heightened violence sexual perversion and materialism by youths. The study focused on the role c f education, family and other social institutions to address die moral issue but disagrees with their irrelevance in checking die deterioration. Furthermore it examined historical values of using jingles to improve the moral standards cf die society and the challenge cf preserving them in the knowledge economy and in die present era of high-tech innovations. Reflecting on the causes and symptoms of moral degeneration, the chapter argued for a renewed focus on methods of imparting moral lessons that are likely to influence positive moral character among the youth with a view to transforming them into responsible adult citizens